2000
DOI: 10.1083/jcb.150.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Regions in a Yeast Myosin-V Tail Domain Are Required for the Movement of Different Cargoes

Abstract: The Saccharomyces cerevisiae myosin-V, Myo2p, is essential for polarized growth, most likely through transport of secretory vesicles to the developing bud. Myo2p is also required for vacuole movement, a process not essential for growth. The globular region of the myosin-V COOH-terminal tail domain is proposed to bind cargo. Through random mutagenesis of this globular tail, we isolated six new single point mutants defective in vacuole inheritance, but not polarized growth. These point mutations cluster to four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 48 publications
4
115
1
Order By: Relevance
“…Our observation that the GTD is required for melanosome targeting agrees with a number of recent studies implicating this domain in cargo binding, most strikingly those involving the yeast type V myosin Myo2p and its interactions with secretory vesicles (Schott et al, 1999) and the vacuole membrane (Catlett et al, 2000). Our demonstration that the GTD is not sufficient for melanosome targeting contrasts, however, with the work on Myo2p, where the ability of its GTD to associate with cargo and to generate a dominant negative phenotype indicates that its GTD is sufficient for targeting (Schott et al, 1999;Catlett et al, 2000).…”
Section: Identification Of Myosin Va Heavy Chain Sequences Required Fsupporting
confidence: 79%
“…Our observation that the GTD is required for melanosome targeting agrees with a number of recent studies implicating this domain in cargo binding, most strikingly those involving the yeast type V myosin Myo2p and its interactions with secretory vesicles (Schott et al, 1999) and the vacuole membrane (Catlett et al, 2000). Our demonstration that the GTD is not sufficient for melanosome targeting contrasts, however, with the work on Myo2p, where the ability of its GTD to associate with cargo and to generate a dominant negative phenotype indicates that its GTD is sufficient for targeting (Schott et al, 1999;Catlett et al, 2000).…”
Section: Identification Of Myosin Va Heavy Chain Sequences Required Fsupporting
confidence: 79%
“…The observation that both Myo2p and Vac17p are mislocalized is consistent with a defect in the association of the Myo2p-Vac17p complex. When myosin motors are defective in forming organelle-specific complexes, the motor and organelle specific receptor are mis-localized (Catlett et al, 2000;Lipatova et al, 2008;Peng and Weisman, 2008). Surprisingly, the levels of Vac17p in the ptc1⌬ mutant are significantly lower than that in a wild-type strain ( Figure 7B).…”
Section: Discussionmentioning
confidence: 87%
“…Both myo2-2p, which is defective in binding Vac17p and myo2p-Y1415E, which is defective in binding Ypt31/32p, are mis-localized (Catlett et al, 2000;Lipatova et al, 2008; data not shown). These observations suggest the possibility that PTC1 regulates organelle inheritance by controlling the association of the Myo2p with organellespecific receptors.…”
Section: Ptc1 Is Required For the Proper Association Of The Vacuole Tmentioning
confidence: 99%
“…8E), suggesting strongly that Myo2-573p retains affinity for Ypt11p. The myo2-573 mutation induces six substitutions (Val 1189 to Ala, Val 1288 to Gly, Lys 1500 to Met, Pro 1529 to Ser, Glu 1546 to Gly, and Lys 1559 to Arg), and none of these overlap with any critical residues, whose substitution is reported to induce defects in the transport of secretory vesicles or vacuoles (8,32). It is conceivable that the myo2-573 mutation reduces the affinity of Myo2p for a factor for mitochondrial distribution.…”
Section: Discussionmentioning
confidence: 99%